The Ion Transport Peptide Is a New Functional Clock Neuropeptide in the Fruit Fly Drosophila melanogaster. - Hermann-Luibl, C.; Yoshii, T.; Senthilan, P.R.; Dircksen, H.; Helfrich-Förster, C. (Journal of Neuroscience, 2014)
The clock network of Drosophila melanogaster expresses various neuropeptides, but a function in clock-mediated behavioral control was so far only found for the neuropeptide pigment dispersing factor (PDF). Here, we propose a role in the control of behavioral rhythms for the ion transport peptide (ITP), which is expressed in the fifth small ventral lateral neuron, one dorsal lateral neuron, and in only a few nonclock cells in the brain. Immunocytochemical analyses revealed that ITP, like PDF, is most probably released in a rhythmic manner at projection terminals in the dorsal protocerebrum. This rhythm continues under constant dark conditions, indicating that ITP release is clock controlled. ITP expression is reduced in the hypomorph mutant Clk(AR), suggesting that ITP expression is regulated by CLOCK. Using a genetically encoded RNAi construct, we knocked down ITP in the two clock cells and found that these flies show reduced evening activity and increased nocturnal activity. Overexpression of ITP with two independent timeless-GAL4 lines completely disrupted behavioral rhythms, but only slightly dampened PER cycling in important pacemaker neurons, suggesting a role for ITP in clock output pathways rather than in the communication within the clock network. Simultaneous knockdown (KD) of ITP and PDF made the flies hyperactive and almost completely arrhythmic under constant conditions. Under light-dark conditions, the double-KD combined the behavioral characteristics of the single-KD flies. In addition, it reduced the flies' sleep. We conclude that ITP and PDF are the clock's main output signals that cooperate in controlling the flies' activity rhythms.